2012
DOI: 10.3727/096368912x640547
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Exploit the Immune Response Mediating Chemokines to Impact the Phenotype of Glioblastoma

Abstract: In contrast to the application of human mesenchymal stem cells (hMSCs) in regenerative medicine, only a limited number of studies are addressing their use in anticancer therapy. As the latter may represent a new hope to improve the survival of patients with glioblastoma multiformae (GBM), the most common and malignant form of the brain tumors, we aimed to investigate the interactions of hMSCs and GBM cells under in vitro conditions. Four hMSC clones and three different GBM cell lines were used to study their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 64 publications
2
49
0
Order By: Relevance
“…These also increased the sensitivity of the glioma cell toward temozolomide. This was consistent with the study of Motaln et al (2012) that human BM-MSCs may promote the senescence of the tumor cells by inducing cell morphology and cytokine changes.…”
Section: Therapeutic Effects Of Mscssupporting
confidence: 80%
“…These also increased the sensitivity of the glioma cell toward temozolomide. This was consistent with the study of Motaln et al (2012) that human BM-MSCs may promote the senescence of the tumor cells by inducing cell morphology and cytokine changes.…”
Section: Therapeutic Effects Of Mscssupporting
confidence: 80%
“…The key finding of our present results is that indirect and direct effects of MSC on GBM U87-MG cells were associated with increased expression levels of both, B1 and B2 receptors, possibly triggering increased invasiveness. By the same token, increased levels of kinin receptor expression would not support previously observed inhibition of invasion of GBM cells in indirect interactions with MSC (9). With respect to the underlying mechanism, Montana and Sontheimer (16) showed that bradykinin via B2R-induced [Ca 21 ] i transients enhanced and directed invasion of glioma cells toward blood vessels.…”
Section: Discussionmentioning
confidence: 72%
“…The indirect co-cultures were set up in duplicates using six-well Transwell inserts (Corning Costar, Sigma) with 0.4 lm pore size and the corresponding six-well plate, as described previously (9). When indirectly co-cultured, MSC were always plated in the bottom and U87 were always plated in the insert at the density of 1.5 3 10 5 cells in 3 ml final volume of media per well and cultured for 72 h. MSC were left to attach for 4 h before adding the inserts with U87 cells.…”
Section: Indirect and Direct Cell Co-culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unaltered stem cells can have inherent anti-tumor properties to factors that are released by stem cells and physical relationship and connections that are recognized among the stem cells and tumor cells [151][152][153]. Stem cells have been established in many different ways to cover up cancer and several are in detail as given below.…”
Section: Development Of Anticancer Stem Cellsmentioning
confidence: 99%